Reservoirs of Porcine Circoviruses: A Mini Review - Zhai, Shao-Lun; Lu, Shou-Sheng; Wei, Wen-Kang; Lv, Dian-Hong; Wen, Xiao-Hui; Zhai, Qi; Chen, Qin-Ling; Sun, Yan-Wei; Xi, Yun (Frontiers in Veterinary Science, 2019)
Porcine circovirus (PCV) is the smallest known DNA virus in mammals. At present, PCVs were divided into three species, PCV1, PCV2 and PCV3. PCV1 and PCV2 was found in 1970s and 1990s, but PCV3 is a newly discovered virus in pigs in 2016. PCV1 does not cause disease in pigs. However, PCV3, similar to PCV2, is reported to be associated with several swine diseases including porcine dermatitis and nephropathy syndrome (PDNS) and reproductive failure. PCVs are very common in domestic pig and wild boar. However, PCVs are occasionally isolated from non-porcine animals, including ruminants (such as cattle, goats, wild chamois, and roe deers), rodents (such as NMRI mice, BALB/c mice, Black C57 mice, ICR mice, Mus musculus, and Rattus rattus), canines (such as dogs, minks, foxes, and raccoon dogs), insects (such as flies, mosquitoes, and ticks) and shellfish. Moreover, PCVs were frequently reported in biological products, including human vaccines, animal vaccines, porcine-derived commercial pepsin product, and lots of cell lines. PCVs were also widely circulating in environmental samples, including water samples and air samples. Interestingly, PCV1 and/or PCV2 antibody or antigen could be detected in human sera, human stool samples and respiratory swab samples, revealing potential zoonotic of PCVs. To summarize, PCVs possess many types of reservoirs. In this review, we summarize the reservoirs of PCVs, which is helpful to understand the natural circulating status and possible cross-species transmission of PCVs.